Structure-controlled electronic structure and electrochemical energy storage mechanisms in Bi-rich BiFeO3 based asymmetric supercapacitor devices - Agrawal, Bhavi; Sharma, Aditya; Chae, Keun Hwa; Varshney, Mayora; Brajpuriya, Ranjeet Kumar; Won, Sung Ok; Kumar, Shalendra (Elsevier BV, 2026)
The correlations among the Bi stoichiometry, secondary phase formation, electronic structure, and electrochemical behaviour have been established in sol-gel auto-combustion prepared Bi1+xFeO3 (x = 0.00–0.10) nanocrystals. A quantitative phase analysis, from Rietveld refined X-ray diffraction (XRD) patterns, conveyed a minimum secondary phase segregation, ~ 4.1 %, in Bi1.05FeO3. The Bi3+ and Fe3+ ions have been confirmed in the Bi1+xFeO3 samples through Fe L-edge and Bi N-edge X-ray absorption spectroscopy (XAS) spectra. The O K-edge XAS spectra indicated a reduction in unoccupied Bi 6sp states and, thus, endorsed the band gap energy decrease, from 2.1 eV to 1.93 eV, and oxygen ion vacancy formation. Electrochemical studies revealed that Bi1.05FeO3 exhibited the highest capacitance of 222.2 F/g and 117.3 F/g in 1 M KOH and 1 M NaOH electrolytes, respectively. An asymmetric supercapacitor device, a Swagelok cell (Bi1.05FeO3//activated carbon, 1 M KOH), has offered a high energy density of 124.9 Wh/kg (at a power density of 1750 W/kg) with 88 % capacitance retention after 10,000 cycles.